Fuzzy multi criteria evaluation for performance of bus companies - Othman, Mahmod; Ku-Mahamud, Ku Ruhana (Academic Journals Database, 2010)
A multi criteria decision making in ranking the bus companies using fuzzy rule is proposed. The proposed method uses the application of fuzzy sets and approximate reasoning in deciding the ranking of the performance of several bus companies. The proposed method introduces data normalization using similarity function which dampens extreme values that exist in the data. The use of the model is suitable in evaluating situation that involves subjectivity, vagueness and imprecise information. Experimental results are comparable to several previous methods.